Editorial: On critique, dissensus and human rights literacies - Roux, C.; Becker, A. (South African Journal of Higher Education, 2017)
Globally, issues such as xenophobia, rising nationalism and populism, linked to the international migrant crisis, are stretching the past influence and the present reinterpretation of the Universal Declaration of Human Rights (1948) to its limits. Locally, the #MustFall[i] protests at higher education institutions rightly question the existence and validity of human rights, especially as it pertains to the right to education, socio-economic rights and the moral responsibility of higher education institutions to its students within human rights policy frameworks. The growing critique of human rights is crucial not only to the understanding of the conceptual, legal, moral, historic and contextual complexities of human rights but also the rethinking of the anthropological, ethical, ontological and epistemological premise of human rights. Human rights literacies, we argue, while including knowledge about human rights, question the social and moral consequences of the (non)realisation of human rights as well as the anthropological, ethical, ontological and epistemological premise of human rights. Critique and dissensus are inherent to human rights literacies and impact on how we speak and act to in(ex)clusions, marginalisation, intolerance, disrespect, misrecognition and discrimination. [i] The unexpected and unprecedented nature of the student protests during 2015-2016 came as a shock to many South Africans. Even naming the protests present some difficulties. Students refer to the protests as a movement. In this article we refer to the student movement as #MustFall which include: #Rhodesmustfall, #Rhodessowhite, #OpenStellenbosch, #TransformWits, #KingGeorgemustfall, #Thestatuemustfall, #Feesmustfall, #Nationalshutdown, #Feeswillfall, #ANCmustfall, #Feeshavefallen, #Rapemustfall and #Partriarchymustfall (Booysen 2016)